PENJADWALAN MESIN SCREW PRESS STASIUN KEMPA PADA PRODUKSI CPO (CRUDE PALM OIL) DAN KERNEL DENGAN MENGGUNAKAN METODE INDIKATOR - Heri Wibowo (Spektrum Industri, 2016)
Complex problems often encountered in the company, especially the production. The company should beable to increase production capability by increasing the utility of existing resources and accuracy in thecompletion of production to match the deadlines set by scheduling planned well. As a company producesCPO and kernel continuously so the scheduling screw press machine should be well planned so thatproduction can be completed on time, damage to the engine and overtime can be avoided. This study aimsto analyze the utilization schedule and screw press machine at the station felt that optimal production canbe achieved and determine the cause of the delay production time resulting in overtime. The method usedis the method of indicators that can be applied to the machine which is parallel with different capacities.This method minimizes the turnaround time by prioritizing machine with a large capacity whilemaintaining the efficiency of the engine and the completion time has been determined. Proposedscheduling using indicators generate optimal schedule, 13840 hours of work available only used 12373.5hours with five machine screw press, the clock difference is 1408.5 hours of work hours are unemployedand 58 hours of treatment machine screw press, and produce five utilities screw press machine onaverage up to 89.40% and utilities average every month five screw press machine is 89.46%. The delaytime of CPO production process and the kernel has been caused by damage to machine screw presswhich occur during the production process takes place so that if the production capacity is reduced andovertime hours cannot be avoided. Screw press machine maintenance can be done by the enginemaintenance schedule time without having to wait for the machine was broken beforehand and this canreduce the cost of production.Keywords : Indicator Method, Scheduling Engine